Design of plate directional heat transmission structure based on layered thermal metamaterials - L. K. Sun; Z. F. Yu; J. Huang (AIP Advances, 2016)
Invisibility cloaks based on transformation optics are often closed structures; however, such a structure limits the kinds of objects that can be placed in the cloak. In this work, we adopt a transformation thermodynamics approach to design an “open cloak”, called a plate directional heat transmission structure, which is capable of guiding heat fluxes to the flank region of the metamaterial device. The most fascinating and unique feature of the device is that the lower surface can remain at a lower temperature compared with the SiO2 aerogel thermal insulation material. Our results are expected to markedly enhance capabilities in thermal protection, thermal-energy utilization, and domains beyond. In addition to the theoretical analysis, the present design is demonstrated in numerical simulations based on finite element calculations.